Characterization of intrahepatic B cells in acute-on-chronic liver failure - Zhao, Yudong; He, Wei; Wang, Chenchen; Cui, Nana; Yang, Changjie; You, Zhengrui; Shi, Bisheng; Xia, Lei; Chen, Xiaosong (Frontiers in Immunology, 2022)
Background and objectives: Acute on chronic liver failure (ACLF) is characterized by the immunologic dissonance during the prolonged pathogenic development. Both abnormal innate immune and adaptive T- cell response have been reported in patients with ACLF, while less is known regarding B cells in ACLF pathogenesis. Previous reports were only based on immunophenotyping of peripheral blood samples. Herein, we aim to dissect liver-infiltrating B cell subpopulation in ACLF. Methods: Paired liver perfusate and peripheral blood were freshly collected from healthy living donors and recipients during liver transplantation. Liver tissues were obtained from patients with acute on chronic liver failure, cirrhosis and healthy controls. Flow cytometry was used to characterize the phenotypic and functional alterations in intrahepatic and circulating B cell populations from ACLF, cirrhosis and healthy controls. The expression of CD19+ and CD138+ on liver tissues was examined by immunohistochemistry staining. Results: In this study, we first deciphered the intrahepatic B cells subsets of ACLF patients. We found the ACLF liver harbored reduced fraction of naïve B cells and elevated percentage of CD27+CD21- activated memory B cells (AMs), CD27-CD21- atypical memory B cells (atMBC)，CD27+IgD-IgM+(IgM+ memory B cells) and CD27+CD38++ plasma cells than cirrhosis and healthy controls. Moreover, these B subpopulations demonstrated enhanced activation and altered effector functions. Specifically, the ACLF liver was abundant in atMBC expressing higher CD11c and lower CD80 molecule, which was significantly correlated to ALT and AST. In addition, we found intrahepatic CD27+CD38++plasma cells were preferentially accumulated in ACLF, which expressed more CD273 (PD-L2) and secreted higher granzyme B and IL-10. Finally, the enriched hepatic plasma B cells were in positive association with disease severity indices including AKP and γ-GGT. Conclusions: In this pilot study, we showed an intrahepatic B cell landscape shaped by the ACLF liver environment, which was distinct from paired circulating B cell subsets. The phenotypic and functional perturbation in atMBC and plasma cells highlighted the unique properties of infiltrating B cells during ACLF progression, thereby denoting the potential of B cell intervention in ACLF therapy.